Decentralization and Local Fiscal Disparity: Comparative Analysis of the General-Purpose Grant for Local Governments in Indonesia and Thailand - wongpreedee, achakorn; sudhipongpracha, tatchalerm (King Prajadhipok’s Institute Journal, 2020)
In the aftermath of the 1997 economic crisis, Indonesia and Thailand adopted decentralization as one of their administrative reform policies. While Indonesia’s decentralization efforts have been touted as a “big-bang” approach, decentralization in Thailand has been noted for its slow progress. This article compares the two countries’ decentralization reforms by examining their local governments’ fiscal conditions in 2011. The article focuses on two sources of local government revenue: revenue raised by local authorities themselves and intergovernmental transfers from the central governments. In this article, provincial-level data on local government finances are analyzed by using several quantitative measures. The findings show that transfers from the national level provide a major source of revenue for local jurisdictions in Indonesia and Thailand. This article argues that despite the decentralization reforms undertaken since the 1990s, local governments in Indonesia and Thailand continue to have limited revenue-generating capacity. Nevertheless, this article demonstrates that the Indonesian local authorities receive more general-purpose grants per capita from Jakarta than their Thai counterparts who heavily rely on purposive and project grants from Bangkok. In other words, local authorities in Indonesia possess more discretion in using their intergovernmental transfers. In addition, the general-purpose grant system in Thailand does not effectively address disparities in local fiscal conditions. Local jurisdictions with strong revenuegenerating capacity and income per capita tend to receive more general-purpose grants than those with weak capacity. In contrast, Indonesia’s general-purpose grant allocation system provides more resources for economically isadvantaged provinces and provinces that experience inter-religious conflicts.